2020
DOI: 10.3390/ijerph17062059
|View full text |Cite
|
Sign up to set email alerts
|

Nine-Year Nationwide Environmental Surveillance of Hepatitis E Virus in Urban Wastewaters in Italy (2011–2019)

Abstract: Hepatitis E virus (HEV) is an emerging causative agent of acute hepatitis worldwide. To provide insights into the epidemiology of HEV in Italy, a large-scale investigation was conducted into urban sewage over nine years (2011–2019), collecting 1374 sewage samples from 48 wastewater treatment plants located in all the 20 regions of Italy. Broadly reactive primers targeting the ORF1 and ORF2 regions were used for the detection and typing of HEV, followed by Sanger and next generation sequencing (NGS). Real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 76 publications
(103 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, by qRT-PCR, HEV RNA was detected in four fecal samples collected from ovine farms. These findings seem to indicate that circulation of HEV among sheep and goat populations in Italy is more frequent than expected and it is not limited to a geographical area (southern Italy), considered at high-risk for human infection [76][77][78], where sustained viral circulation was demonstrated in pig herds or among wild boars [58,79,80]. In our analysis, many of the positive flocks were close to each other (Figure 2), remaining confined within an area of approximately 29.8 km 2 in Piemonte and 14.9 km 2 in Valle d'Aosta.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by qRT-PCR, HEV RNA was detected in four fecal samples collected from ovine farms. These findings seem to indicate that circulation of HEV among sheep and goat populations in Italy is more frequent than expected and it is not limited to a geographical area (southern Italy), considered at high-risk for human infection [76][77][78], where sustained viral circulation was demonstrated in pig herds or among wild boars [58,79,80]. In our analysis, many of the positive flocks were close to each other (Figure 2), remaining confined within an area of approximately 29.8 km 2 in Piemonte and 14.9 km 2 in Valle d'Aosta.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that there was high similarity (98.4%) between study sequence INMI1804_2018 and MN251650, a sequence identified in Italian wastewater [ 30 ]. This finding reinforces evidence, already described by other countries, that inadequate management of sewage treatment plants could represent a critical factor for environmental HEV transmission, including on cultivated land [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current ‘endgame’ of the Global Polio Eradication Program, sewage surveillance is used to detect any residual poliovirus circulation in endemic countries and provide early warning of import of poliovirus. Sewage surveillance has been studied for other enteric viruses [ 5 , 6 ] and for antimicrobial resistance [ 7 ].…”
Section: Introduction: the Concept Of Sewage Surveillancementioning
confidence: 99%